Transport and retention of artificial and real wastewater particles inside a bed of settled aerobic granular sludge assessed applying magnetic resonance imaging - Florian Ranzinger (Water Research X, 2020)
The removal or degradation of particulate organic matter is a crucial part in biological wastewater treatment. This is even more valid with respect to aerobic granular sludge and the impact of particulate organic matter on the formation and stability of the entire granulation process. Before the organic part of the particulate matter can be hydrolyzed and finally degraded by the microorganism, the particles have to be transported towards and retained within the granulated biomass. The understanding of these processes is currently very limited. Thus, the present study aimed at visualizing the transport of particulate organic matter into and through an aerobic granular sludge bed. Magnetic Resonance Imaging (MRI) was successfully applied to resolve the different fractions of a granular sludge bed over time and space. Quantification and merging of 3D data sets allowed for a clear determination of the particle distribution within the granular sludge bed. Dextran coated super paramagnetic iron oxide nanoparticles (SPIONs, dp = 38±10 nm) served as model particles for colloidal particles. Microcrystalline cellulose particles (dp = 1–20 μm) tagged with paramagnetic iron oxide were applied as a reference for toilet paper, which is a major fraction of particulate matter in domestic wastewater. The results were supplemented by the use of real wastewater particles with a size fraction between 28 and 100 μm. Colloidal SPIONs distributed evenly over the granular sludge bed penetrating the granules up to 300 μm. Rinsing the granular sludge bed proved their immobilization. Microcrystalline cellulose and real wastewater particles in the micrometer range accumulated in the void space between settled granules. An almost full retention of the wastewater particles was observed within the first 20 mm of the granular sludge bed. Moreover, the formation of particle layers indicates that most of the micrometer-sized particles are not attached to the biomass and remain mobile. Consequently, these particles are released into the bulk phase when the granulated sludge bed is resuspended.